Interaction between the flagellum of Candidatus Liberibacter asiaticus and the vitellogenin-like protein of Diaphorina citri significantly influences CLas titer - Peng, Tao; Yuan, Yingzhe; Huang, Aijun; He, Jun; Fu, Shimin; Duan, Shuo; Yi, Long; Yuan, Chenyang; Yuan, Huizhu; Wang, Xuefeng; Zhou, Changyong (Frontiers in Microbiology, 2023)
Huanglongbing (HLB) is a global devastating citrus disease, mainly caused by “Candidatus Liberibacter asiaticus” (CLas). It is mostly transmitted by an insect Asian citrus psyllid (ACP, Diaphorina citri) in a persistent proliferative manner. CLas traverse multiple barriers to complete an infection cycle which should be involved in multiple interactions with D. citri. However, the protein-protein interactions between CLas and D. citri are largely unknown. Here, we presented a vitellogenin-like protein (Vg_VWD) in D. citri that interacts with a CLas flagellum (flaA) protein. Vg_VWD is up-regulated in the CLas-infected D. citri. Silencing of Vg_VWD in D. citri via RNAi silencing significantly increased CLas titer, suggesting Vg_VWD plays an important role in CLas- D. citri interaction. Agrobacterium mediated transient expression assays indicated that Vg_VWD inhibits BAX and INF1-triggered necrosis and suppresses callose deposition induced by flaA in Nicotiana benthamiana. These findings provide new insights into the molecular interaction between CLas and D. citri.